The COVID-19 and Filipino Migrant Workers: Looking into the Philippine Government's Post-COVID-19 Support Mechanism - Aubrey D. Tabuga; Anna Rita P. Vargas; Madeleine Louise S. Bai\~no (Philippine Institute for Development Studies (PIDS), 2022)
The COVID-19 was an unprecedented event that tested the capacity of the Philippine government in keeping migrant workers and their families protected and secured. It was not only a matter of simple repatriation process, but this also entailed a multi-dimensional system that encompasses repatriation, health interventions (e.g., testing for COVID-19, treatment, and health monitoring), accommodation and logistical support for quarantine, and economic interventions in the form of financial grants to eligible workers, among others. Existing policy frameworks have guided government response whenever applicable, however nothing has prepared the system for the scale of effects that the COVID-19 pandemic has brought. Thus, managing the influx of returning overseas migrants in the tens and even hundreds of thousands required no less than a whole-ofnation approach. Government agencies involved were forced to expand their networks, innovate their systems, and adapt to the changing events. This entailed a range of interrelated activities and programs that were facilitated by close collaboration and consistent communication among various actors. Based on the findings of the paper, it is crucial to build on the existing digital systems created during this period, strengthen newly formed and existing partnerships, reexamine OFW's insurance and social protection coverage, and consider the creation of, or expansion of existing, contingency fund to address future events of similar nature and magnitude.
Keywords: 330; overseas Filipino workers; COVID-19 response; migration policy; crisis management